ANALYSIS THE DIVERSITY AND DESIGN MEANING OF PROBOLINGGO PANDALUNGAN BATIK MOTIFS - Nur Mauliska; Couteau, Jean (Universitas Islam Zainul Hasan Genggong, 2024)
This research aims to explore the various batik patterns typical of Probolinggo City that reflect its cultural identity. Through a descriptive qualitative approach, data were collected from primary and secondary sources to provide an in-depth understanding of the uniqueness of the batik patterns. The research findings show that Probolinggo Batik, particularly Pandalungan Batik, creates its own identity image through its unique combination of colors and patterns. Various batiks, such as Batik Manggur, Batik Angin Gending, Batik 1000 Taman, Batik Bherungen, and Batik Kali Banger, each reflect aspects of daily life and cultural heritage of Probolinggo City. Through carefully selected patterns and colors, these batiks not only become beautiful works of art, but also become a reflection of the rich cultural identity and diversity of Probolinggo City. In conclusion, Probolinggo Batik is not just a craft, but also a cultural heritage that depicts the rich nature, social life, and folklore of the city. Thus, these batiks not only perpetuate the cultural heritage, but also become a reflection of the strong local identity and cultural pride of Probolinggo City.